Queer call-out - Pelucio, Larissa [UNESP] (2020)
In this paper Tall out is triggered as a metaphor that helps us to think about the forms of political action through which the presumption of moral superiority based on a kind of truth/purity/identity mark came to disallow public speaking by researchers(s) through the demoralization not of their ideals or theories and research results, but of the privileges that were attributed to them and that could be read in their bodies. Finally, we propose to think of the cuier as an alliance and theory to combat identity traps. We insist on its potential contestation and its theoretical capacity to offer conceptual tools for action as well as for reflection against naturalized violence.